Slaying the Nuclear Dragon: Disarmament Dynamics in the Twenty-First Century - Ogilvie-White, Tanya; Santoro, David (Studies in Security and International Affairs, 2012)
In recent decades the debate on nuclear weapons has focused overwhelmingly on proliferation and nonproliferation dynamics. In a series of Wall Street Journal articles, however, George Shultz, William Perry, Henry Kissinger, and Sam Nunn called on governments to rid the world of nuclear weapons, helping to put disarmament back into international security discussions. More recently, U.S. president Barack Obama, prominent U.S. congressional members of both political parties, and a number of influential foreign leaders have espoused the idea of a world free of nuclear weapons. Turning this vision into reality requires an understanding of the forces driving disarmament forward and those holding it back. Slaying the Nuclear Dragon provides in-depth, objective analysis of current nuclear disarmament dynamics. Examining the political, state-level factors that drive and stall progress, contributors highlight the challenges and opportunities faced by proponents of disarmament. These essays show that although conditions are favorable for significant reductions, numerous hurdles still exist. Contributors look at three categories of states: those that generate momentum for disarmament; those with policies that are problematic for disarmament; and those that actively hinder progress-whether openly, secretly, deliberately, or inadvertently. Nuclear deterrence was long credited with preventing war between the two major Cold War powers, but with the spread of nuclear technology, threats have shifted to other state powers and to nonstate groups. Slaying the Nuclear Dragon addresses an urgent need to examine nuclear disarmament in a realistic, nonideological manner.